Means of unitary operators, revisited - Haagerup, Uffe; Kadison, Richard V.; Pedersen, Gert K. (MATHEMATICA SCANDINAVICA, 2007)
It is proved that an operator with bound not exceeding $(n-2)n^{-1}$ in a $C^*$-algebra is the mean of $n$ unitay operators in that algebra.